Optimalisasi Modul Bimbingan Kelompok Islami Untuk Melatih Keterampilan Manajemen Waktu Akademik Siswa Madrasah Tsanawiyah - Damayanti, Putri Eka; Azmi, Khilman Rofi' (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Optimization of Islamic Group Guidance Modules to Practice Academic Time Management Skills Madrasah Tsanawiyah Students. This study aims to determine the development of Islamic group guidance modules to train academic time management skills of class VIII B students at MTs Sunan Prawoto. Knowing the results of expert validation, Indonesian Language Teachers and Guidance and Counseling Teacher practitioners and the feasibility of Islamic group guidance modules to train academic time management skills for class VIII B students at MTs Sunan Prawoto. The method used in this research is the research and development (R&D) method. Research and development research is used to produce certain products and determine the feasibility of these products. The research subjects were 1 material expert, 1 media expert, 1 Indonesian language teacher, 3 Guidance and Counseling teachers, 1 class VIII B guardian, and 10 students of class VIII B. The results concluded that the percentage of validation from material experts got a score of 69.3 %, media experts got a score of 93.1%, and the percentage of validation from Indonesian Language Teachers got a score of 90.7%. Furthermore, the results of the last assessment by 3 Guidance and Counseling Teachers with percentage gains of 91.4%, 93.5%, and 89.5%. Overall, the percentage results obtained in a very good category, because the percentage results are in the interval assessment, namely 80%-100%, with a very good category, the development of the Islamic group guidance module is appropriate for Guidance and Counseling Teachers to train academic time management skills for class VIII B students in MTs Sunan Prawoto. Keywords: Module; Islamic Group Guidance; Academic Time Management